A Review Of Body Shaming Behavior On The Hadith; The Preventive Measurement From Islamic Point Of View - M. Fahmi Azhar; Ida Rochmawati Yusuf (Al-Bukhari : Jurnal Ilmu Hadis, 2022)
This article examines one of the social problems in society which is currently a global issue, namely body shaming behavior. Body shaming behavior is an act of commenting, criticizing or bullying someone's physical (body condition) with the aim of humiliating, because the physical condition of the individual is considered not in accordance with the applicable body image standards and deserves to be commented on. This study examines the behavior of body shaming from the perspective of the hadith. This study seeks to find a correlation between body shaming behavior described in the hadith and explores the preventive actions offered from Islamic perspective. The method used is qualitative-descriptive through library research. The results of this study are 1). Hadith narrated by Tirmidhi: 2502 in general explains how the prophet's view of body shaming behavior is. 2). The meaning of the hadith content in it is an invitation to stay away from body shaming behavior. 3). Impact on victims of body shaming behavior in a psychological perspective. 4). Preventive actions offered to prevent body shaming behavior.